Dynamic Stacking of an Expected Branch Point Adenosine in Duplexes containing Pseudouridine-Modified or Unmodified U2 snRNA Sites - Kennedy, Scott D. (Biochem Biophys Res Commun, 2019)
The pre-mRNA branch point sequence (BPS) anneals with a pseudouridine-modified region of the U2 small nuclear (sn)RNA, and offers a 2′ hydroxyl group of a bulged adenosine as the nucleophile for the first catalytic step of pre-mRNA splicing. To increase our structural understanding of branch site selection, we characterized a duplex containing a BPS sequence that is common among multicellular eukaryotes (5´-UACUGAC-3´) and the complementary U2 snRNA site using NMR. A major conformation of the expected branch site adenosine stacked within the duplex and paired with the conserved pseudouridine of the U2 snRNA strand. In contrast, the guanosine preceding the branch site appeared flexible and had weak contacts with the surrounding nucleotides. Pseudouridine-modified and unmodified U2 snRNA–BPS-containing duplexes remained structurally similar. These results highlight the importance of auxiliary factors to achieve the active bulged conformation of the branch site nucleophile for the first step of pre-mRNA splicing.